Application of Collaborative Learning with Mind Mapping Method on Ecosystem Material For Science Subjects - Septiarini, Rizki Dwika; Prasetiyo, Andika Eko (Islamic Journal of Integrated Science Education (IJISE), 2024)
Teachers are encouraged to have the ability to develop learning strategies and models that are in accordance with the curriculum and student learning styles. Teachers who deliver material with a lecture model will dominate the learning process, so students will tend to behave passively by only listening to the explanation of the material presented. Combining the collaborative learning model with the mind mapping method is expected to improve students' activeness and social relationships. The purpose of this study was to determine how the application of collaborative learning with the mind mapping method affects ecosystem material in science subjects. This research was conducted on March 23, 2024, with the 35 7th grade students of SMPN 1 Plosoklaten. The method used in this research is descriptive analysis with a qualitative approach. The learning model applied can improve personal relationships between students and increase creativity. Therefore, the collaborative learning model with the mind mapping method can be applied in the learning process of science subjects on ecosystem material in grade 7 SMPN 1 Plosoklaten.